Estimating geometric primitives using 3D range data - Berglund, Tomas (Luleå tekniska universitet, EISLAB, 1999)
Master's Thesis at the Department of Mathematics and at the Division of Robotics at the Department of Computer Science and Electrical Engineering, Luleå University of Technology, Sweden Godkänd; 1999; 20110809 (ysko)